Amino acid transporter SLC38A3 promotes metastasis of non-small cell lung cancer cells by activating PDK1. (1st May 2017) - Wang, Yanhui; Fu, Li; Cui, Minqing; Wang, Yongbin; Xu, Yan; Li, Molin; Mi, Jun
Abstract: Background: Tumor metastasis is a finely-tuned pathological process coupled to metabolic reprogramming that includes both glutamine and glucose. The solute carrier SLC38A3, a member of amino acid/polyamine/organocation (APC) superfamily, is anl -glutamine transporter. It is not clear whether SLC38A3 involves the metastasis of NSCLC (non small cell lung cancer). Methods: The scratch test and transwell assay were used to determine the ability of NSCLC to migrate. Cellular amino acids content was determined by mass spectrometry. The cellular response to glutamine/histidine deficiency was evaluated in A549 cells. The expression of SLC38A3 was assayed in clinical NSCLC and paratumor tissues by histoimmunochemistry staining. A nude mouse model of NSCLC metastasis was developed by tail vein injection of tumor cells. Results: SLC38A3 was upregulated in metastatic NSCLC cells and its expression was correlated with prognosis of NSCLC patients. SLC38A3 overexpression promoted epithelial – mesenchymal transition (EMT) and migration of HCC827 and A549 human lung adenocarcinoma cells, and accelerated tumor metastasis in mice. We found that SLC38A3 decreased the cellular concentrations of glutamine and histidine, and the deficiency of glutamine or histidine activated PDK1/AKT signaling that in turn, triggered NSCLC metastasis. Conclusions: SLC38A3 activated PDK1/AKT signaling and promoted metastasis of NSCLC through regulating glutamine and histidine transport, suggesting SLC38A3 as a potential therapeutic target for treatment of NSCLC.